2020
DOI: 10.1111/cas.14532
|View full text |Cite
|
Sign up to set email alerts
|

5‐Fluorouracil resistance mechanisms in colorectal cancer: From classical pathways to promising processes

Abstract: Colorectal cancer (CRC) is a public health problem. It is the third most common cancer in the world, with nearly 1.8 million new cases diagnosed in 2018. The only curative treatment is surgery, especially for early tumor stages. When there is locoregional or distant invasion, chemotherapy can be introduced, in particular 5‐fluorouracil (5‐FU). However, the disease can become tolerant to these pharmaceutical treatments: resistance emerges, leading to early tumor recurrence. Different mechanisms can explain this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
278
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(293 citation statements)
references
References 99 publications
5
278
1
9
Order By: Relevance
“…Although the antimetabolite 5-fluorouracil (5-FU) has been the only drug available to successfully improve 12-month survival in CRC patients, clinical resistance is continuing to be a challenge to date [ 60 ]. The combination strategy has become especially important in CRC due to frequent resistance to 5-FU and different anti-cancer drugs that are administered at or close to the maximally tolerated dose [ 61 , 62 ]. Studies showed a synergistic cytotoxic effect of ATRA when combined with 5-FU in CRC and other cancer types [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the antimetabolite 5-fluorouracil (5-FU) has been the only drug available to successfully improve 12-month survival in CRC patients, clinical resistance is continuing to be a challenge to date [ 60 ]. The combination strategy has become especially important in CRC due to frequent resistance to 5-FU and different anti-cancer drugs that are administered at or close to the maximally tolerated dose [ 61 , 62 ]. Studies showed a synergistic cytotoxic effect of ATRA when combined with 5-FU in CRC and other cancer types [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, based on the drugs being administered, chemoresistance in CRC can also arise due to drug metabolism and specific targets/enzymes [12,13,17]. These two modes of resistance tend to be specific to the drug being administered, since different chemotherapeutics are targeted or metabolised by different targets/enzymes.…”
Section: Drug Resistance In Crcmentioning
confidence: 99%
“…Most of these chemotherapeutic drugs function by interfering with the synthesis of RNA and DNA [11]. The antimetabolite pyrimidine analogue 5-FU [12] does so by incorporating itself into the DNA or RNA and by inhibiting the thymidylate synthases (TYMS) enzyme responsible for synthesising deoxythymidine monophosphate (dTMP) [13]. The platinum drugs, OXA and cisplatin interfere with the synthesis of DNA by acting as intercalating agents, forming intrastrand adducts between two purine residues (two guanine residues or between an adenine and guanine residue) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is a fluorinated pyrimidine antimetabolite, which irreversibly inhibits the enzyme thymidylate synthase and prevents cell proliferation by reducing the thymidine formation required for DNA synthesis [ 54 ]. It is widely used to treat breast, colorectal, and gastric cancers, but it showed several serious side effects such as toxic cardiac reaction, myelosuppression, mucositis, nausea, emesis, and development of resistance [ 55 , 56 ].…”
Section: Antimetabolitesmentioning
confidence: 99%